Intermediator in information seeking process - Janiūnienė, Erika (Information & Media, 1997)
Since 1993 Lithuanian users have been able to search information in the Internet. The network is a part of information infrastructure. It provides possibilities of information accessibility, searching, manipulation and using. However, in order to use Internet as an information resource not only technical means, but also basic knowledge of information seeking methods in the network is needed. Taking into account the possibilities of Internet services and its present using, it could be maintained, that the users and the specialist-intermediators are not prepared enough for this new information activity. So now the main problem is the training of users and the intermediators. In this article I survey the intermediator’s role in information seeking process and analyze user’s groups, which used network for information seeking.